Stability Mechanism and Repair Method of U-Shaped Steel Reverse Arch Support in Soft Floor Roadway - Chao Wang; Xiaoyi Chen; Jiandong Zhang; Yongping Wu (Advances in Civil Engineering)
This paper is aimed at the inverted arch support instability of track roadway with mining level +1100 m in Liuyuanzi Coal Mine. By means of field investigation, theoretical analysis, numerical calculation, and engineering practice, the instability reasons of inverted arch structure are expounded, the mechanical mechanism of instability of inverted arch structure is revealed, and the “sliding-rotating beam” for the instability of inverted arch structure is put forward. Based on Fenner’s formula and mechanics principle, the equilibrium equation of “sliding-rotating beam” is given. The results show the following: Firstly, the insufficient stiffness at the joint of the inverted arch structure and the U-shaped steel support on the floor is the key reason for the floor instability. Secondly, when the action stress of the “sliding-rotating beam” is less than the critical value, three kinds of instability modes of the inverted arch structure may occur, that is, sliding upward, rotating upward, or sliding-rotating upward. Each instability criterion and critical value are also different. Considering the axisymmetric condition, the critical value calculation formula of the three modes can be simplified into one formula. Thirdly, the equivalent friction factor restricts the stability of the “sliding-rotating beam,” and there is a “breaking point.” The relationship between the equivalent friction factor and the action stress of the “sliding-rotating beam” is “class hyperbola.” When the equivalent friction factor is greater than the “breaking point value,” the “sliding-rotating beam” may remain stable. Moreover, with the increase of equivalent friction factor, the action stress required for the stability of the “sliding-rotating beam” is smaller, and it tends to be more stable. The breaking point value of equivalent friction factor is 18.6. Finally, 36U-shaped steel round frame with bolt-mesh-shotcrete-combined support is applied to improve the equivalent friction factor and the foot stiffness of U-shaped support in roadway. After two months of on-site implementation, the floor heave was reduced by 69.1%. In conclusion, the theoretical analysis is correct and the control method is effective.